2017
DOI: 10.1007/s40618-017-0700-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor and progesterone receptor protein and gene expression in papillary thyroid carcinomas: associations with histological features

Abstract: We provide evidence for the expression pattern of VDR, PR and CYP24A1 in the progression of PTC. Rapid anti-tumor responses of vitamin D in PTC may be blocked due to inactivation of local vitamin D metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…[56] Vitamin D receptor (VDR) polymorphisms has been demonstrated to have an impact on Vitamin D metabolism in thyroid tissue, which may modulate the anti-tumor effect of Vitamin D in papillary thyroid cancer (PTC). [57] VDR expression in human thyroid cancer cells has been linked to increased ECM protein-1 (ECM1) and type II trans-membrane serine protease-4 (TPMRSS4) expression, which are tissue markers of increased local invasion and metastasis,[58] highlighting the potential role of Vitamin D analogues in down regulating VDR and thus having a beneficial impact on thyroid cancer. Studies have shown that the efficacy of VDR agonist therapy to decrease viable thyroid cancer cell count depends on the FF FokI VDR genotype polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…[56] Vitamin D receptor (VDR) polymorphisms has been demonstrated to have an impact on Vitamin D metabolism in thyroid tissue, which may modulate the anti-tumor effect of Vitamin D in papillary thyroid cancer (PTC). [57] VDR expression in human thyroid cancer cells has been linked to increased ECM protein-1 (ECM1) and type II trans-membrane serine protease-4 (TPMRSS4) expression, which are tissue markers of increased local invasion and metastasis,[58] highlighting the potential role of Vitamin D analogues in down regulating VDR and thus having a beneficial impact on thyroid cancer. Studies have shown that the efficacy of VDR agonist therapy to decrease viable thyroid cancer cell count depends on the FF FokI VDR genotype polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…One area of intrigue is the role of vitamin D in metastatic papillary thyroid cancer, particularly bone metastases. Clinckspoor et al [ 38 ] and Yavropoulou et al [ 39 ] identified differential expression of the vitamin D receptor and vitamin D enzymatic regulators in those PTCs prone to metastasis. Specifically, the tissue from lymph node metastasis had decreased expression of VDR when compared to the primary tumor.…”
Section: Vitamin D and Papillary Thyroid Carcinomamentioning
confidence: 99%
“…Overexpression of VDR may affect the kinetics of vitamin D binding, thereby downregulating the effects of the protein complex on VDRE and effectively altering the downstream transcription of various proteins involved in tumorigenesis. Yavropoulou et al [ 39 ] studied 45 thyroid samples from patients with PTC, finding both higher VDR and CYP24A1 expression in samples of malignant tissue. In addition, increased CYP24A1 expression was associated with lymph node metastasis.…”
Section: Other Metabolitesmentioning
confidence: 99%
“…Knowing the role of CITED1 in PC and the epidemiological evidence of higher incidence in females, it is not surprising to find expression of oestrogen and progesterone receptors in papillary carcinoma. Expression of oestrogen receptor alpha and progesterone receptor has been reported in 19% and 38.7-57% of PC cases, correspondingly [73,74].…”
Section: Immunohistochemistry Of Thyroid Neoplasmsmentioning
confidence: 99%
“…Cancer cells also possess vitamin-D inactivating 24-hydroxylase but not activating enzyme, namely, 1-alpha-hydroxylase. Overexpression of 24-hydroxylase is associated with extrathyroid invasion and lymph node metastases [74].…”
Section: Immunohistochemistry Of Thyroid Neoplasmsmentioning
confidence: 99%